Rate of depression in late-life in superannuated government employed center of ‎Guilan University of medical sciences - naeima khodadady; farzaneh sheikholeslami; shadman rezamasuoleh; mohamadali yazdani (Guilan University of Medical Sciences, 2007)
Introduction: Aging is a word used for decreased life abilities with diminished biological ‎morbid. Emotional disorders make up a group of late‏ ‏‎-‎‏ ‏life mental disorders. The most ‎common disorder in elderly is depression. Statistical data show that about ‎‏20‏‎% of American ‎elderly have depression who are usually misdiagnosed and don t receive proper treatment and ‎this disturbs their life process knowing socio - demographic factors and elderly depression can ‎help nurses to better assess their needs and pay more attention to elderly depression.‎ Objective: The aim is to determine the level of depression and its relationship with socio - ‎demographic characteristics in Rasht city in ‎‏2007‏‎.‎ Methods: This is a correlational descriptive study and ‎‏100‏‎ samples were randomly ‎chosen from elderly of superannuated government employed center.‎‏ ‏The data ‎collection instrument consisted of a two part questionnaire. The first part included ‎twenty personal demographic questions and ‎‏11‏‎ questions regarding social ‎characteristics. The second part included DVYSS standard depression scale with ‎‏30‏‎ ‎questions, which is a two point test in two levels of “Yes” and “No” response and ‎‏5‏‎ ‎‏±‏‎ ‎‏4‏‎ score indicates normal, ‎‏15‏‎ ‎‏±‏‎ ‎‏6‏‎ show mild depression and ‎‏23‏‎ ‎‏±‏‎ ‎‏5‏‎ is sever ‎depression. Finally, the study data were analyzed by descriptive – analylitic statistics ‎and SPSS software. ‎ Results: Finding showed that ‎‏45‏‎.‎‏3%‏‎ of samples had mild and sever depression. ‎Depression is elderly had a significant relationship with married statues (p<‎‏0.007‏‎), ‎satisfaction with place of living (p<‎‏0.000‏‎), use of medicine (p<‎‏0.006‏‎), living with ‎spouse and children (p<‎‏0.0005‏‎), emotional support of family, members (p<‎‏0‏‎.‎‏01‏‎), ‎emotional support of friends (p<‎‏0‏‎.‎‏01‏‎), emotional support of others (p<‎‏0‏‎.‎‏04‏‎), ‎satisfaction with relations (p<‎‏0‏‎.‎‏001‏‎) and satisfaction with overall support (p<‎‏0‏‎.‎‏01‏‎).‎ Conclusion: Current study demonstrates that a significant number of elderly suffer ‎from depression and factors such as drug use, lack of satisfaction with place of ‎living, loneliness, low family, friends and others, emotional support, lack of ‎satisfaction with communication and support are effective in establishing depression.‎